Extracorporeal Shock Wave Combined with Traditional Chinese Medicine Bone-setting Manipulation for External Humeral Epicondylitis: A Randomized Clinical Trial - Yu, Changsui; Xu, Zifeng; Zhu, Liguo; Zhang, Xiaofeng; Yu, Zhongbao; Zhan, Fengyuan; Yu, Xin; Wang, Shuren; Lu, Kejian; Li, Junjie; et al. (Journal of Sports Medicine and Therapy, 2024)
Objective: The purpose of this study was to evaluate the clinical efficacy of extracorporeal shock waves combined with traditional Chinese medicine bone-setting manipulation for external humeral epicondylitis. Methods: Ninety-two patients with external humeral epicondylitis were randomly divided into an observation group and a control group. Patients in the control group were treated with extracorporeal shock waves while those in the observation group with traditional Chinese medicine bone-setting manipulation based on the control group. Patients in both groups were evaluated by the Visual Analogue Scale (VAS), Mayo Elbow Performance Score (MEPS), and Disabilities of the Arm, Shoulder, and Hand Questionnaire (DASH) before and after treatment. The inflammatory factors such as IL-6, IL-10, TNF-ɑ, and clinical outcomes were contrasted before and after treatment. Results: There were statistically significant differences in VAS score, MEPS score, and DASH score between the two groups before and after treatment (p < 0.05). The observation group exhibited a more pronounced improvement in each score compared to the control group. Post-treatment, the inflammatory factors of both groups were significantly lower than pre-treatment levels (p < 0.05), with the observation group showing a more noticeable decrease. The overall effectiveness of the observation group was higher than that of the control group, and the difference was statistically significant (p < 0.05). Final considerations: The combination of extracorporeal shock wave therapy and traditional Chinese medicine bone-setting manipulation can effectively alleviate pain symptoms and improve dysfunction caused by external humeral epicondylitis, while also reducing inflammatory factor expression. This combined treatment may prove more effective than extracorporeal shock wave therapy alone. Clinical Trial: Registration: ChiCTR2200066075.